2016
DOI: 10.1002/nau.23078
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐term outcomes of a male retro‐urethral, transobturator synthetic sling for treatment of post‐prostatectomy incontinence: Impact of radiotherapy and storage dysfunction

Abstract: The AdVance sling provides mid-term improvement in men with PPI. However, men with radiotherapy or DO have significantly poorer outcomes with mid-term results indicating a return to baseline degree of incontinence. Caution should be taken when considering the AdVance sling in these men. Pre-op urodynamics in men with radiotherapy and/or overactive bladder may be important when considering men for AdVance sling. Neurourol. Urodynam. 36:1147-1150, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…The majority of previous studies assess the success of the AdVance sling using improvement in daily pad use and quality of life questionnaires . Recently, two small Australian series have reported on the outcomes of the AdVance sling . Habashy et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of previous studies assess the success of the AdVance sling using improvement in daily pad use and quality of life questionnaires . Recently, two small Australian series have reported on the outcomes of the AdVance sling . Habashy et al .…”
Section: Discussionmentioning
confidence: 99%
“…10,11,14 Recently, two small Australian series have reported on the outcomes of the AdVance sling. 15,16 Habashy et al reviewed 50 patients with mild or moderate incontinence treated with the AdVance sling at a median (range) follow-up time of 36 (14-72) months and reported that men were using an average of 1.02 PPD, 1.84 PPD less in comparison to before their procedure. They also reported an increasing mean PPD usage with time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Men with DO appear to have worse continence outcomes after a retroluminal transobturator (AdVance ® ) sling surgery (36-38). Conversely, the presence of DO does not seem to worsen the continence outcome post AUS surgery (27,28).…”
Section: Post Pr Detrusor Overactivitymentioning
confidence: 99%
“…Habashy et al reported on 20 patients with PC who had the AdVance ® sling, and PC is not predictive of worse continence outcome. However, they did not report on the post-sling incidence of renal failure or hydronephrosis (36). …”
Section: Post Prostatectomy Impaired Bladder Compliancementioning
confidence: 99%